DNA damage in tumor cells and peripheral blood lymphocytes of endometrial cancer patients assessed by the comet assay - Buchynska, L.G.; Brieieva, O.V.; Lurchenko, N.P.; Protsenko, V.V.; Nespryadko, S.V. (Experimental Oncology, 2017)
To date, genome instability is considered to be a common feature not only of tumor cells, but also of non-malignant cells of cancer patients, including peripheral blood lymphocytes (PBLs). The issue of the association between genome instability in tumor cells and PBLs, as well as of its relationship with tumor progression remains poorly understood. Aim: To evaluate the level DNA damage in tumor cells and PBLs of endometrial cancer (EC) patients with regard to clinical and morphological characteristics of the patients. Materials and Methods: DNA damage was assessed in 106 PBLs samples and 42 samples of tumor cell suspension from EC patients by comet assay. PBLs from 30 healthy women were used as control. The level of DNA damage was expressed as the percentage of DNA in the comet tails (% tail DNA). Results: It was revealed that the amount of DNA damage in PBLs of EC patients was 2.2 times higher in comparison with that of healthy donors (8.3 ± 0.7 and 3.7 ± 0.4% tail DNA, respectively) (p < 0.05). In this study, no association between the levels of DNA damage in endometrial tumor cells and PBLs was observed (r = 0.11; p > 0.05). The amounts of DNA damage both in tumor cells and PBLs were not related to the degree of tumor differentiation as well as the depth of myometrial invasion, but depended on the body mass index (BMI) of EC patients: high level of lesions was observed in patients with elevated BMI values. Furthermore, the level of DNA damage in tumor cells was associated to familial aggregation of cancer and was significantly higher in endometrial cells from patients with family history of cancer vs that from EC patients with sporadic tumors (32.3 ± 2.9 and 22.8 ± 1.8% tail DNA, respectively) (p < 0.05). It was also found that for women who had high level of DNA damage in PBLs, the risk of EC was greater (odds ratio value of 3.5) compared to those with low level of such lesions. Conclusion: Genome instability that appears as an increased level of DNA damage in tumor cells and PBLs of EC patients is associated with BMI and family history of cancer and can reflect a predisposition to cancer.